Análise da relação entre concentração bancária e spread para o setor bancário no Brasil no período de 2003 a 2010 - Correia, Marcelo Wesley Justino (2015)
The Brazilian banking market has undergone a series of transformations during the 1990s, which had an impact on the ways of acting banks directly affecting aspects related to efficiency, profitability / return and exposure to systemic risk of banks. From the mid-1990s,with the implementation and consolidation of the Real Plan, there were changes in the Brazilian economy for a scenario of economic stability from containing inflation and other economic policies to such a scenario. From this perspective after this restructuring process, there was a higher concentration of the Brazilian banking sector environment. This study investigated the relationship between bank concentration and banking spread as well as a set of explanatory factors that influence variations that banking spread. The results of the econometric model diverged from the central hypothesis in this research, that a more concentrated structure could contribute to a reduction in the general banking spread. According to this research the concentration could prove negatively related to spread through increased process efficiency and loss reduction including indirect reduction in default levels. But what was observed by econometric evidence was the existence of a positive relationship between these two variables in the model analyzed in this research, it can be seen from the positive estimated coefficient for the relationship between the banking spread and the measure represented bank concentration by MSCB1 variable in the econometric model.